Photoelectrochemical hydrogen evolution using CdTexS1−x quantum dots as sensitizers on NiO photocathodes. Issue 2 (21st December 2020) - Benazzi, Elisabetta; Cristino, Vito; Boaretto, Rita; Caramori, Stefano; Natali, Mirco
Abstract : Stable photocurrents (up to ∼1 h) are obtained using CdTe x S1− x QDs on NiO photocathodes with molecular Ni(ii ) or metallic Pt HECs. Abstract : The design of active photocathodes for the hydrogen evolution reaction (HER) is a crucial step in the development of dye-sensitized photoelectrochemical cells (DS-PECs) aimed at solar-assisted water splitting. In the present work, we report on the use of orange CdTe x S1− x quantum dots (QDs) with an average diameter of ca. 3.5 nm, featuring different capping agents (MAA, MPA, and MSA ) for the sensitization of electrodes based on nanostructured NiO. Photoelectrochemical characterization of the resulting NiO|QDs electrodes in the presence of [Co III (NH3 )5 Cl]Cl2 as an irreversible electron acceptor elects MAA -capped QDs as the most active sample to achieve substantial photocurrent densities thanks to both improved surface coverage and injection ability. Functionalization of the NiO|QDs electrodes with either heterogeneous Pt or the molecular nickel bis(diphosphine) complex (1 ) as the hydrogen evolving catalysts (HECs) yields active photocathodes capable of promoting hydrogen evolution upon photoirradiation (maximum photocurrent densities of −16(±2) and −20(±1) μA·cm −2 for Pt and 1 HECs, respectively, at 0 V vs. NHE, 70–80% faradaic efficiency, maximum IPCE of ca. 0.2%). The photoelectrochemical activity is limited by the small surface concentration of the QD sensitizers on the NiO surface and the competitive light absorption by the NiO material which suggests that the match between dye adsorption and the available surface area is critical to achieving efficient hydrogen evolution by thiol-capped QDs.